2022
DOI: 10.1186/s12877-022-03590-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the well-being of Asian American LGBT individuals across the lifespan: perspectives from leaders of community-based organizations

Abstract: Background Lesbian, gay, bisexual, and transgender (LGBT) individuals have documented disparities in mental health that are experienced across the life course. However, limited research has been conducted to identify the factors which contribute to evaluated risk for poor mental health among older Asian Americans who identify as LGBT. The purpose of this study was to determine the perspectives of leaders of community-based organizations about the mental health needs and concerns of their LGBT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Consider persons with marginalized identities, like members of the lesbian, gay, bisexual, transgender, queer, intersex, asexual, and more community, as an example. Research has demonstrated that parental and family rejection are contributing factors to psychological distress, especially among Asians (Matthews et al, 2022). In such scenarios, families may not only withhold support but additionally become a direct source of stressors (e.g., hurtful languages, expected conformity) toward the individual.…”
Section: Decision About Fcdmmentioning
confidence: 99%
“…Consider persons with marginalized identities, like members of the lesbian, gay, bisexual, transgender, queer, intersex, asexual, and more community, as an example. Research has demonstrated that parental and family rejection are contributing factors to psychological distress, especially among Asians (Matthews et al, 2022). In such scenarios, families may not only withhold support but additionally become a direct source of stressors (e.g., hurtful languages, expected conformity) toward the individual.…”
Section: Decision About Fcdmmentioning
confidence: 99%